Efficacy and Safety of Ashwagandha (Withania somnifera) Root Extract in Improving Sexual Function in Women: A Pilot Study - Dongre, Swati (Biomed Res Int, 2015)
Background. Many women experience sexual dysfunction where there are orgasm disorders and sexual difficulties. Ashwagandha (Withania somnifera) is a herb known to improve the body's physical and psychological condition. Objective. The purpose of the study was to determine the efficacy and safety of a high-concentration ashwagandha root extract (HCARE) supplementation for improving sexual function in healthy females. Methods. In this pilot study, 50 study subjects were randomized to either (i) HCARE-treated group or (ii) placebo- (starch-) treated group. The subjects consumed either HCARE or placebo capsules of 300mg twice daily for 8 weeks. Sexual function was assessed using two psychometric scales, the Female Sexual Function Index (FSFI) Questionnaire and the Female Sexual Distress Scale (FSDS), and by the number of total and successful sexual encounters. Results. The analysis indicates that treatment with HCARE leads to significantly higher improvement, relative to placebo, in the FSFI Total score (p < 0.001), FSFI domain score for “arousal” (p < 0.001), “lubrication” (p < 0.001), “orgasm” (p = 0.004), and “satisfaction” (p < 0.001), and also FSDS score (p < 0.001) and the number of successful sexual encounters (p < 0.001) at the end of the treatment. Conclusions. This study demonstrated that oral administration of HCARE may improve sexual function in healthy women. The present study is registered in the Clinical Trial Registry, Government of India, with a number CTRI/2015/07/006045.